Kajian Lanskap Budaya sebagai Identitas Budaya di Kampung Adat Kuta, Kabupaten Ciamis - Hafifah Akbar; Imam Indratno (UNISBA Press, 2023)
Abstract. The Kuta Indigenous People are located in Ciamis Regency. The indigenous people of Kuta are closely related to the natural environment, culture and are still bound by traditions that have been passed down from generation to generation. The purpose of this research is to identify the cultural landscape, and develop an eco-culture based tourism plan in Kampung Kuta. The researcher used the structuralism approach method and used the cultural landscape analysis method. The results of the analysis of the cultural landscape produce a formal identity that is formed from Leuweung Gede's spiritual values ​​with the existence of traditional and spiritual activities. This spiritual value is a manifestation of natural and cultural values ​​towards ambu rama or ancestors. Then in substantial identity emerges the cultural value of the tritangtu philosophy in bhuana where the manifestation of this philosophical concept is to regulate and maintain human attitudes, both with others and with nature and God. The resulting value is constructed as a new value creation (friendship value) which will later be used for tourism development in Kampung Kuta. The implementation of the development of eco-culture tourism is carried out by developing eco-culture tourism products, namely offering tour packages. In addition, by conducting training to improve the quality of tourism human resources. Eco-cultural tourism activities can be supported by improving accessibility and basic facilities based on the DED documents of Kampung Kuta, Ciamis Residence. Abstrak. Masyarakat Adat Kuta terletak di Kabupaten Ciamis. Masyarakat adat Kuta erat hubungannya dengan lingkungan alam, budaya dan masih terikat dengan adat istiadat yang turun-temurun. Tujuan dari penelitian ini adalah mengidentifikasi lanskap budaya, dan mengembangkan rencana paiwisata berbasis eco-culture di Kampung Kuta. Penulis menggunakan metode pendekatan strukturalisme serta menggunakan metode analisis lanskap budaya. Hasil analisis lanskap budaya menghasilkan identitas formal yang terbentuk dari nilai spiritual Leuweung Gede dengan adanya aktivitas adat dan spiritual. Nilai spiritual ini merupakan manifestasi dari nilai alam dan budaya terhadap ambu rama atau leluhur. Kemudian pada identitas substansial muncul nilai budaya dari filosofi tritangtu di bhuana dimana manifestasi dari konsep filosofi tersebut untuk mengatur dan menjaga sikap manusia, baik dengan sesama maupun dengan alam dan Tuhan. Nilai yang dihasilkan di konstruksi sebagai penciptaan nilai baru (nilai sahabat) yang nantinya digunakan untuk pengembangan pariwisata di Kampung Kuta. Implementasi pengembangan eco-culture tourism dilakukan dengan pengembangan produk eco culture tourism yaitu menawarkan paket-paket wisata. Selain itu juga dengan melakukan pelatihan-pelatihan untuk meningkatan kualitas sumber daya manusia pariwisata. Kegiatan wisata eko-budaya dapat ditunjang dengan perbaikan aksesibilitas dan fasilitas dasar berdasarkan dokumen DED Kampung Kuta, Kabupaten Ciamis.